DEFENSE CONCEPT THROUGH THE LEGISLATURE - PROTECTING VALUES FOR THE SUSTAINABILITY OF SOCIETY (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2025)
The pivotal function of independent institutions in the adjudication of legally binding decisions, in accordance with the rule of law and the fundamental principles of the Latvian legal system, is evident. These institutions serve to clarify and adjust the applicability of general concepts to specific cases that are the subject of dispute. The unique geopolitical situation of Latvia is a perpetual reminder of the ambiguity with which its state institutions are regarded by the public and other state-level actors. A fundamental and diametrically opposed clash of opinions within the framework of the state itself (between various stakeholders, members of society, political players, institutions) and in the mass media environment, inciting long-term disagreements and turbulence, can literally be created by a few words or one sentence, one illustration, from the context of which the author's opinion on global issues of Latvian history and political position can be interpreted more broadly. The concept of militant democracy involves the potential questioning and challenging of the very guarantees of defending freedoms and human rights. The article provides a critical overview of the latest amendments to legislation and court practice, thereby establishing a unique insight into the ability and methods of all three powers of the state in strengthening and defending state values in times of turbulence.